The benefits of fiscal consolidation in uncharted waters - Philipp Rother; Ludger Schuknecht; Jürgen Stark (European Central Bank (ECB), 2010)
This paper looks at fiscal sustainability and fiscal risks from a comprehensive, global perspective. It argues that the benefits of consolidation have to be re-assessed given that industrialised countries have entered uncharted waters with unsustainable public debt dynamics and enormous contingent liabilities across sectors and countries coinciding with strong, non-linear and potentially highly adverse fiscal-financial interlinkages. This suggests that there would be significant benefits from fiscal consolidation without delay and that there is a need for caution against excessive faith in fiscal engineering.
Keywords: C32; E3; E43; E58; 330; Consolidation; deficits; financial crisis; Fiscal sustainability; public debt; tail risks; Haushaltskonsolidierung; Öffentliche Schulden; Haushaltsdefizit; Finanzpolitik; Nachhaltigkeit; Finanzkrise; EU-Staaten; Welt